IMPLEMENTASI MEDIA SMART TV DAN MATERI AJAR BERBASIS DIGITAL PADA PEMBELAJARAN PAI DI SDN 11 LOLONG KOTA PADANG - Shintia Mulyawati; Zulbaidah Zulbaidah; Afnibar Afnibar; Ulfatmi Ulfatmi (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study aims to describe the implementation of Smart TV and digital-based teaching materials in Islamic Religious Education (PAI) learning at Lolong 11 Public Elementary School, Padang City. The research method used was descriptive qualitative with a field study approach, through observation, interviews, and documentation with the principal, teachers, and students. The results indicate that the use of Smart TV as a learning medium can increase student interest in learning, facilitate understanding of religious concepts, and create a more interactive learning environment. The visual and contextual presentation of digital materials has been proven to assist teachers in conveying Islamic Religious Education (PAI) values ​​more effectively. These findings demonstrate that digital media-based learning not only addresses the challenges of developing educational technology but also strengthens the internalization of spiritual values ​​in the context of modern learning. In conclusion, the implementation of Smart TV and digital materials has a positive impact on improving the quality of Islamic Religious Education (PAI) learning, particularly in terms of effectiveness, interactivity, and relevance to students' lives in the digital era.